2014
DOI: 10.1186/preaccept-1129034223134684
|View full text |Cite
|
Sign up to set email alerts
|

Acute diarrhea in adults consulting a general practitioner in France during winter: incidence, clinical characteristics, management and risk factors

Abstract: BackgroundData describing the epidemiology and management of viral acute diarrhea (AD) in adults are scant. The objective of this study was to identify the incidence, clinical characteristics, management and risk factors of winter viral AD in adults.MethodsThe incidence of AD in adults during two consecutive winters (from December 2010 to April 2011 and from December 2011 to April 2012) was estimated from the French Sentinelles network. During these two winters, a subset of Sentinelles general practitioners (G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 12 publications
2
14
0
1
Order By: Relevance
“…The risk of transmission seems to play a subordinate role as a reason for inability to work. Similar findings were reported in a French study where 79% of working patients were on sick leave for a median duration of 3 days [ 35 ]. In a Danish study, only 35% of patients with AG reported having missed work or school as a result of illness [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The risk of transmission seems to play a subordinate role as a reason for inability to work. Similar findings were reported in a French study where 79% of working patients were on sick leave for a median duration of 3 days [ 35 ]. In a Danish study, only 35% of patients with AG reported having missed work or school as a result of illness [ 34 ].…”
Section: Discussionsupporting
confidence: 90%
“…It is well known that some pathogens causing AG are easily transmitted from human-to-human, especially viruses, and contact with diarrhoea patients has been described as a risk factor for AG previously [ 35 , 36 ]. In our study, 28.6% (95% CI 24.9–32.6) of the patients had contact to other people suffering from similar signs and symptoms in the 7 days preceding symptom onset.…”
Section: Discussionmentioning
confidence: 99%
“…There are several possible explanations for the observed GI symptoms during an ARI. First, each winter, ARIs and gastroenteritis outbreaks overlap, creating a spurious association between ARI and GI symptoms, maybe caused by a co-infection between respiratory agents and enteroviruses [16]. Second, GI symptoms may be a side effect of drug treatment (antibiotic or antiviral) [17,18] or food consumption (ex: raw shellfish and molluscs) [19].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, person-to-person transmission by contact or from aerosols generated by vomit presents an added difficulty [21][22][23]. This is consistent with the relatively high incidence of norovirus in the population and its periodic emergence [2,[24][25][26][27][28]. The involvement of exposure to vomit shown in the multivariate analysis is explained by the episodes of vomiting experienced by many affected students in the school restrooms, classrooms, and corridors.…”
Section: Discussionmentioning
confidence: 56%